Trachoma Prevalence After Discontinuation of Mass Azithromycin Distribution. (13th February 2020) - Godwin, William; Prada, Joaquin M; Emerson, Paul; Hooper, P J; Bakhtiari, Ana; Deiner, Michael; Porco, Travis C; Mahmud, Hamidah; Landskroner, Emma; Hollingsworth, T Déirdre; Medley, Graham F; Pinsent, Amy; et al.
Abstract: Background: As the World Health Organization seeks to eliminate trachoma by 2020, countries are beginning to control the transmission of trachomatous inflammation–follicular (TF) and discontinue mass drug administration (MDA) with oral azithromycin. We evaluated the effect of MDA discontinuation on TF1–9 prevalence at the district level. Methods: We extracted from the available data districts with an impact survey at the end of their program cycle that initiated discontinuation of MDA (TF1–9 prevalence <5%), followed by a surveillance survey conducted to determine whether TF1–9 prevalence remained below the 5% threshold, warranting discontinuation of MDA. Two independent analyses were performed, 1 regression based and 1 simulation based, that assessed the change in TF1–9 from the impact survey to the surveillance survey. Results: Of the 220 districts included, TF1–9 prevalence increased to >5% from impact to surveillance survey in 9% of districts. Regression analysis indicated that impact survey TF1–9 prevalence was a significant predictor of surveillance survey TF1–9 prevalence. The proportion of simulations with >5% TF1–9 prevalence in the surveillance survey was 2%, assuming the survey was conducted 4 years after MDA. Conclusion: An increase in TF1–9 prevalence may represent disease resurgence but could also be due to measurement error. Improved diagnostic tests are crucial to elimination of TF1–9 as a public health problem.